Anaplasma phagocytophilum, Babesia microti, and Borrelia burgdorferi in Ixodes scapularis, Southern Coastal Maine - Mary S. Holman; Diane A. Caporale; John Goldberg; Eleanor H. Lacombe; Charles B. Lubelczyk; Peter W. Rand; Robert P. Smith (Emerging Infectious Diseases, 2004)
Ixodes scapularis (deer ticks) from Maine were tested for multiple infections by polymerase chain reaction and immunofluorescence. In 1995, 29.5%, 9.5%, and 1.9% of deer ticks were infected with Borrelia burgdorferi, Anaplasma phagocytophilum, and Babesia microti, respectively. In 1996 and 1997, the number of A. phagocytophilum-infected ticks markedly declined. In 1995 through 1996, 4 (1.3%) of 301 were co-infected.